Comparative study on phenol and naphthalene steam reforming over Ni-Fe alloy catalysts supported on olivine synthesized by different methods. (15th July 2018) - Meng, Junguang; Zhao, Zengli; Wang, Xiaobo; Zheng, Anqing; Zhang, Dongyan; Huang, Zhen; Zhao, Kun; Wei, Guoqiang; Li, Haibin
Highlights: Environmentally friendly and industrially promising catalysts with satisfactory effects on tar reforming were prepared. Fe existed in different forms in the TF-Ni/Fe/olivine (Fe2 O4 2− ) and WI-Ni/Fe/olivine (Fe2 O3 ) catalysts. The TF-Ni/Fe/olivine showed more stable catalytic performance than that of WI-Ni/Fe/olivine. The carbon deposits produced by naphthalene catalytic cracking were difficult to react with steam. Abstract: Ni/Fe bimetallic catalysts were synthesized on an olivine support using the wetness impregnation (WI) and thermal fusion (TF) methods, and catalytic cracking and steam reforming on different tar model compounds (phenol and naphthalene) were investigated in a fixed bed reactor. The effects of the reaction temperature and space-time on the catalytic cracking activity of phenol and naphthalene were tested, and the influences of steam on the carbon molar ratio (S/C) and different synthesized methods on the steam reforming of phenol and naphthalene were also studied. In addition, the carbon deposited on the catalyst was analysed using temperature program oxidation (TPO), Raman spectroscopy and transmission electron microscopy (TEM) methods. The elemental composition of the catalyst was analysed by X-ray fluorescence (XRF), and the physiochemical properties of the catalysts were characterized via X-ray diffraction (XRD), the BET surface area, scanning electron microscopy (SEM), TEM, Raman spectroscopy, temperature program reduction (TPR), and X-ray photoelectron spectroscopy (XPS). The results showed that the structure of TF-Ni/Fe/olivine changed considerably compared with that of calcined olivine (mainly the Mg2 SiO4 phase) and that a portion of Fe was fused into the olivine structure and reorganized into a new (Mg, Fe) Fe2 O4 phase. After reduction, the Ni-Fe alloy was detected on both catalysts, and the particle size of the Ni-Fe alloy on TF-Ni/Fe/olivine was smaller than that of WI-Ni/Fe/olivine. The TF-Ni/Fe/olivine cracked phenol into small-molecule gas (CO and H2 ) and a small quantity of olefin. By contrast, phenol was polymerized to naphthalene in the absence of a catalyst. The phenol and naphthalene steam reforming conversion on WI-Ni/Fe/olivine were both higher than that of TF-Ni/Fe/olivine. A 100-h stability test of phenol steam reforming on TF-Ni/Fe/olivine and WI-Ni/Fe/olivine was conducted, and TF-Ni/Fe/olivine showed higher stability in the early stages of the experiment due to stronger interactions between the active sites and olivine support. The deposited carbon from naphthalene steam reforming was more difficult to eliminate because it contained more Cβ and Cγ, which had higher degrees of graphitization.